Practical innovation in measuring chlorophyll content of Peranggi chili toward the student learning outcomes - Irvan Ariansyah; Entin Daningsih; Reni Marlina (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
Practicum is a learning method that involves students in experiments to understand concepts in depth. One concept that is often considered abstract is chlorophyll, which formation is influenced by environmental factors such as water availability. To clarify this concept, a practicum on chlorophyll extraction from peranggi chili (Capsicum annum L. Var Chinensis) under drought stress was conducted, while introducing local plants to students. The innovation in this practicum lies in the use of color reference sheets as visual indicators. This study aimed to measure learning outcomes and students' responses to the practicum. This study usesed a quantitative descriptive method with instruments in the form of teaching modules, LKPD, psychomotor and affective observation sheets, and response questionnaires. This research consisted of three stages. The first stage of preparation included making and validating instruments. The implementation stage included chlorophyll extraction activities, observations with color reference, psychomotor and affective assessments, and questionnaire filling. Data analysis was carried out by calculating and categorizing data based on Riduwan's categories. The results showed the acquisition of cognitive (85.85), psychomotor (95%), and affective (93%) scores with a very high category, as well as a student response of 81%. This practicum is a new innovation in chlorophyll observation with a simple method and low cost, so it can be applied in schools.